Theoretical Study of Freedom of Movement of Human Limbs and Restrictive Conditions After Injury to The Limbs (Eurasian Journal of Learning and Academic Teaching, 2023)
In the article, the theoretical study of the freedom of movement of the human limbs and the limiting conditions as a result of damage to the limbs. We will tell you in detail about the types of injuries and the classification of injuries in the article. In this article, we can discuss the study of the freedom of movement of the limbs and the limiting consequences as a result of injury